Worker productivity during lockdown and working from home: evidence from self-reports - Etheridge, Ben,Wang, Yikai,Tang, Li (Institute for Social and Economic Research, 2020)
We examine self-reported productivity of home workers during lockdown using survey data from the UK. On average, workers report being as productive as at the beginning of the year, before the pandemic. However, this average masks substantial differences across sectors, by working from home intensities, and by worker characteristics. Workers in industries and occupations characterized as being suitable for home work according to objective measures report higher productivity on average. Workers who have increased their intensity of working from home substantially report productivity increases, while those who previously always worked from home report productivity declines. Notable groups suffering the worst average declines in productivity include women and those in low-paying jobs. Declines in productivity are strongly associated with declines in mental well-being. Using stated reasons for productivity declines, we provide evidence of a causal effect from productivity to well-being.
10419/248579
Keywords: Graue Literatur; Arbeitspapier; Coronavirus; Lockdown; Telearbeit; Arbeitsproduktivität; Psychische Krankheit; Familie-Beruf; Großbritannien; Worker Productivity; Working From Home; COVID-19; Sectors; Inequality; Gender; Mental Well-Being